Evaluation of the vestibular and ocular motor screening (VOMS) as a prognostic tool for protracted recovery following paediatric sports-related concussion - Gregory Knell; Todd Caze; Scott O Burkhart (BMJ Open Sport & Exercise Medicine)
Objective To understand the relationship between initial vestibular and ocular motor screening (VOMS) and recovery time, and the utility of VOMS to screen for protracted recovery in youth/adolescent patients with sport-related concussion (SRC).Methods Participants (8–18 years) who were diagnosed with an SRC within 7 days of the injury were administered the VOMS test by certified medical personnel. Recovery time (days) and protracted recovery (>30 days) were the primary outcomes. Multivariable regression models were used to evaluate the association between VOMS symptom provocation and (1) recovery time (days) and (2) protracted recovery. Measures of VOMS validity, predictive ability and receiver operator curves were used to assess VOMS as a prognostic tool to accurately classify a normal/protracted recovery.Results After adjustment, any symptom provocation across all VOMS domains was associated (p<0.05) with greater recovery time, except the convergence test (p=0.08) in females. All VOMS test thresholds (≥1 to ≥10) in males and (≥1 to ≥5) in females were associated (p<0.05) with recovery time. However, the VOMS test performed poorly among males (receiver operating characteristic (ROC) area=0.66) and failed among females (ROC area=0.56) as a prognostic tool to identify those that will have a normal/protracted recovery.Conclusion In this sample, overall, the VOMS test was associated with recovery time (days); however, the VOMS was not a valid stand-alone prognostic tool to identify a delayed recovery, but may be useful in combination with other concussion symptomology assessments. Future studies should confirm these findings in larger samples while taking into consideration other comorbid factors that may influence recovery time.